Conductance Simulation of the Purinergic P2X(2), P2X(4), and P2X(7) Ionic Channels Using a Combined Brownian Dynamics and Molecular Dynamics Approach - Turchenkov, Dmitry A.
This paper investigates the application of an original combined approach of molecular and Brownian dynamic methods with quantum chemistry calculations for modeling the process of conductance of ion channels using purinergic P2X family receptors P2X(2), P2X(4), and P2X(7) as a case study. A simplified model of the ionic channel in the lipid bilayer has been developed. A high level of conductance (30 pS) of P2X(2) ionic channel together with the key role of Asp(349) in forming the selectivity filter of P2X(2) has been shown by using this approach. Calculated P2X(2) permeability to monovalent cations Li+, Na+, and K+ conforms to the free diffusion coefficient of these ions, which shows the low selectivity of P2X(2) ionic channel.